The EU recovery strategy: A blueprint for a more social Europe or a house of cards? - Silvia Rainone; Philippe Pochet (European Trade Union Institute (ETUI), 2022)
This paper explores the EU recovery strategy with a specific focus on its potentially transformative aspects vis-à-vis European integration and on its implications for the social dimension of the EU's socio-economic governance. It aims, in particular, to provide a reflection on whether the established measures put forward sufficient safeguards against the spectre of austerity and on whether these constitute steps towards disfranchising social and labour policies from being used as 'variables' of economic growth. Our analysis suggests that the EU recovery strategy has taken remarkable steps in the direction of a more solidaristic and socially embedded Union. However, the foundations of this progress are fragile. European political leaders must ensure that the measures taken are just a first step and are translated into structural reforms. Without changes to the Union's regulatory and governance framework, the only barrier to economic downturns being translated into socially regressive policies is political will.
Keywords: 330